Sex differences and cultural diversity in perceptions toward eSports between American and Chinese university students - Xianhua Luo; Li Chen (Cogent Social Sciences)
Market demand for video gamers and the popularity of electronic sports (eSports) competitions have become central to collegiate students’ activities, including tournaments, professional teams, and academic programs. This study aimed to identify the factors affecting American and Chinese college students’ perceptions of eSports, focusing on sex or cultural differences. A pre-validated and reliability-tested questionnaire—the Profile of Esports Perception—was used to collect data from 679 participants regarding attraction, economics, recognition, socialization, and technicity. A 2 × 2 factorial multivariate analysis of variance and separate analyses of variance were performed to examine data interactions and simple main effects. The results indicated a significant interaction effect between nation and sex and the five noted perceptual factors. American students scored lower than Chinese students on economics, recognition, socialization, and technicity. Female participants scored lower than male participants on all perceptual factors. Sex differences and cultural diversity present challenges for eSports game developers and policymakers in the US and China. Future research should explore the motivations of eSports gamers.